New Media, Knowledge Practices and Multiliteracies: HKAECT 2014 International Conference - Ma, W.W.K (Springer, 2016)
This volume highlights key aspects of new media, knowledge practices and multiliteracies in communication and education, providing readers with a range of empirical findings, novel theories and applications. The reports also include best practices, case studies, innovative solutions and lessons learned with regard to three core fields: (1) New media: discussions on the effects of traditional and new media, legal risks concerning social media, the effects of media intervention on help-seeking attitudes, obstacles of using tablets for learning, qualitative interpretation of media reporting, use of social media for enhancing design practices, and news-reading habits; (2) Knowledge practices: exploration of online viewing and lifestyles, reform of school management models, undergraduate students’ mathematics learning experiences, perceived accounting ethics and online knowledge sharing, creating knowledge repositories, digital technologies outside school, smartphone usage and life satisfaction, and cultural differences and isomerism; and (3) Multiliteracies: studies on learning style inventories, the impact of ICT in interdisciplinary approaches, ePortfolios for learning, video production and generic skills enhancement, mobile-assisted collaborative learning, and the effects of project-based learning on student achievements. The reports presented are from various countries and organizations.